Corpo próprio, especialidade e mundo percebido em Merleau-ponty - Figueiredo, Jadismar de Lima (2015)
This study it constitutes in a dissertation based on a bibliographic background in which was used as the main source the philosophy’s title ‘Phenomenology of Perception’ by Maurice Merleau-Ponty. Its aim is to analyze the concept of one’s own body and its related spatiality discussed in the mentioned work of the philosopher. At first, it is presented an issue concerning what is the concept of body perceived by physiology as a juxtaposed structure. On the other hand, Merleau-Ponty points to a new understanding of the body, not as constituted bodies, but as one’s own body that is able to recognize its very existence as a living subject, as it is situated in space and not just positioned into it. Trailing the sense of spatiality, Merleau-Ponty discusses about it not in the same wayas addressed by Geography, in which it is possible to think of locations, but still as a point in space where the subject can notice his own body, as perceiver subject. It is the experienced world, lived, in which the subject can recognize his own existence. The notion of space can’t be understood as isolated parts, but with modalities that are associated to the subject. Considering these concepts, it explores also other topics such as intentionality and motricity. The first as a tendency of the one’s own body "to go further" because of its intention to do so and the second as an extension of the body to be able to appropriate the phenomena perceived in order to understand them. It also discusses the concept of perceived world in which the perceiver subject perceives the phenomena and the world in perspective. In addition, he is not alone, as there are other perceiver subjects that carry a peculiarity of ‘I myself’ responsible for the redefinition of the world and the phenomena appropriation through perspectives. There is ‘I myself’ in others, but this can’t be broken into, what is known of it is just what is expressed, communicated. Hence, the importance of the language that is present throughout the discussion not only as verbal language, but as body grammar.